Teacher Approaches to Boosting Student Motivation in English Learning - Huda, Moh. Choirul (STKIP PGRI Tulungagung, 2024)
This research aims to analyze the strategies used by teachers to increase the motivation of 10th-grade students in learning English and the factors influencing these teaching strategies. Using a qualitative descriptive methodology, this research targets English teachers and 10th-grade students at SMKN I Boyolangu. Data collection involved interviews with the 3 teacher and 10 students. The data analysis process included data reduction, data display, drawing conclusion. From the interviews to the teachers, it was found that in teaching listening skills, the teacher uses Online Videos, Podcasts, Dictation. For teaching speaking skills, Role Plays, Debates, Group Discussions, Presentations, Storytelling are applied. In reading skills instruction, Reading Circles, Guided Reading strategy are employed. For writing skills, Graphic Organizers, Peer Review, and Collaborative Writing strategy are used because students often struggle to develop their writing. The use of these strategies has shown to increase students' motivation in learning English. This is evidenced by the student difficulty index, which indicates that the exercises are of medium difficulty, making them manageable for the students without being too easy or too difficult.